EKSISTENSI HAK ULAYAT DI INDONESIA - Rosalina Rosalina (SASI, 2010)
Communal Land Rights is the right of the highest land tenure of indigenous people. Indigenous groups is a unity that has a specific area, have a legal entity, has the authority and has its own wealth. rights applicable exit and into the Communal Land. into force because the only alliance in the sense that all citizens can reap the rewards of the land and all plants and animals that hidupdalam fellowship area. The right of association was substantially restrict freedom of the citizen as an individual effort, for the sake of fellowship. Valid exit, because instead of the customary law community, in principle, not allowed to participate received his/ working the land which is the fellowship area concerned. Only with the permission of the fellowship as well as pay compensation outsiders can get a chance to participate and use communal land. Along with the development of life, then the use of communal land is not only used to meet together, but also members of the public are allowed to use some lands to be used to meet their individual needs. Individual mastery of this process continues for generations and isrecognized by the indigenous people.